The participation of states in international organisations : the role of human rights and democracy - Duxbury, Alison, 1970- (Cambridge, UK : Cambridge University Press, 2011)
'The admission of a state to membership is an important decision for an international organisation. In making this determination, organisations are increasingly promoting the observance of human rights and democratic governance as relevant principles. They have also applied the same criteria in resolving the question of whether existing members should be excluded from an organisation's processes. Through a systematic examination of the records, proceedings and practice of international organisations, Alison Duxbury examines the role and legitimacy of human rights and democracy as membership criteria. A diverse range of examples is discussed, including the membership policies and practice of the League of Nations and the United Nations; the admission of the Central and Eastern European states to the European Union; developments in regional organisations in Africa, Asia and the Americas; and the exclusion of members from the UN specialised agencies'--
'International organisations are increasingly promoting human rights and democratic governance as principles relevant in deciding applications for admission by non-member states. In the 1990s the importance of these standards was underlined by suggestions that a state's membership of institutions such as the United Nations and its involvement in regional security measures should be based on adherence to certain fundamental values, including democracy. Not only have human rights and democracy norms been utilised in determining the admission of a potential member to an international organisation, but they have also been taken into account in resolving the question whether existing members, or their representatives, should be excluded from an organisation's processes. Such determinations have been made in the Commonwealth, the Organization of American States and in decisions to deny accreditation to delegations in the General Assembly of the United Nations. When organisations have ignored these principles in their membership policies their choices have been criticised - as was the case when the Association of Southeast Asian Nations admitted Burma in 1997'--
Machine generated contents note: Introduction; 1. The move to institutions in the age of rights; 2. The challenge of universality: the League of Nations and United Nations; 3. Rights, regionalism and participation in Europe; 4. Restricting the ranks: excluding states from closed organisations; 5. The relationship between powers, purposes and participation in specialised organisations; 6. Legitimacy, democracy and membership; Conclusion.
Includes bibliographical references and index.
Keywords: International agencies -- Membership; Human rights; Democracy